Discordance Between Creatinine-Based and Cystatin C–Based Estimated GFR: Interpretation According to Performance Compared to Measured GFRPlain-Language Summary - Yeli Wang; Ogechi M. Adingwupu; Michael G. Shlipak; Alessandro Doria; Michelle M. Estrella; Marc Froissart; Vilmundur Gudnason; Anders Grubb; Roberto Kalil; Michael Mauer; Peter Rossing; Jesse Seegmiller; et al. (Kidney Medicine, 2023)
Rationale & Objective: Use of cystatin C in addition to creatinine to estimate glomerular filtration rate (estimated glomerular filtration rate based on cystatin C [eGFRcys] and estimated glomerular filtration rate based on creatinine [eGFRcr], respectively) is increasing. When eGFRcr and eGFRcys are discordant, it is not known which is more accurate, leading to uncertainty in clinical decision making. Study Design: Cross-sectional analysis. Setting & Participants: Four thousand fifty participants with measured glomerular filtration rate (mGFR) from 12 studies in North America and Europe. Exposures: Serum creatinine and serum cystatin C. Outcome(s): Performance of creatinine-based and cystatin C–based glomerular filtration rate estimating equations compared to mGFR. Analytical Approach: We evaluated the accuracy of eGFRcr, eGFRcys, and the combination (eGFRcr-cys) compared to mGFR according to the magnitude of the difference between eGFRcr and eGFRcys (eGFRdiff). We used CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) equations to estimate glomerular filtration rate. eGFRdiff was defined as eGFRcys minus eGFRcr and categorized as less than −15, −15 to <15, and ≥15 mL/min/1.73 m2 (negative, concordant, and positive groups, respectively). We compared bias (median of mGFR minus eGFR) and the percentage of eGFR within 30% of mGFR. Results: Thirty percent of participants had discordant eGFRdiff (21.0% and 9.6% negative and positive eGFRdiffs, respectively). In the concordant eGFRdiff group, all equations displayed similar accuracy. In the negative eGFRdiff groups, eGFRcr had a large overestimation of mGFR (−13.4 [−14.5 to −12.2] mL/min/1.73 m2) and eGFRcys had a large underestimation (9.9 [9.1-11.2] mL/min/1.73m2), with opposite results in the positive eGFRdiff group. In both negative and positive eGFRdiff groups, eGFRcr-cys was more accurate than either eGFRcr or eGFRcys. These results were largely consistent across age, sex, race, and body mass index. Limitations: Few participants with major comorbid conditions. Conclusions: Discordant eGFRcr and eGFRcys are common. eGFR using the combination of creatinine and cystatin C provides the most accurate estimates among persons with discordant eGFRcr or eGFRcys.